Singularities of Solutions of One Class of Equations of Continuum Mechanics - Il'man, V. M.; Kapustyan, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We analyze one class of families of integral equations and describe the dependence of the singularities of solutions of integral equations on the dimensions of the families of kernels of equations. On the basis of these results, we propose procedures for the construction of approximate solutions for a small parameter.